Efektivitas konseling kelompok terkait pendidikan seksual pada masa anak-anak akhir - Patrika, Fauziah Julike (Fakultas Psikologi Universitas Hang Tuah, 2024)
Sexual harassment is not only prevalent to the grown-ups. The underage frequently happens to be the victims of this appalling behaviour. The common cause of the phenomenon is insufficient sexual education. An intervention is considered necessary to minimise the sexual harassment prevalence, one of which is through group counselling. This experimental research was designed in a one group pretest-posttest approach to identify the effectiveness of group counselling on sexual education. The group counselling will be conducted through psychoeducation and feedback. The intervention has five sessions of 90-120 minutes each. There are five chosen participants using a purposive sampling method. Data analysis using one sample t-test shows that the group counselling positively enhances ones’ sexual education knowledge and comprehension. The intervention provides education expected to enhance self-protection mechanisms of child against sexual harassment or even sexual abuse.